The potential of contingent valuation for public administration practice and research - Weimer, David L. (2005)
Public administrators and policy analysts routinely face the task of assessing goods whose social values are not revealed in markets. Often "structured conversations" with citizens provide the only source of information for valuing of such goods. The problem of valuation is particularly great in the case of environmental amenities that may have value to people beyond their direct consumption. In response, environmental economists have developed a methodology, contingent valuation (CV), for estimating the social value of policy changes using data from questions posed to samples of survey respondents. Although contingent valuation is beginning to be applied to other policy areas, it has not yet seen general widespread use. This article provides an overview of the CV methodology and speculates on its future use of public administrators. - Reproduced.
Keywords: Research; Public administration